Linear Cryptanalysis of Block Ciphers in the Cluster Computational Environment - Kyuregyan, Melsik; Manukyan, Ofelya; Harutyunyan, Edita (Mathematical Problems of Computer Science, 2021)
This paper presents some results concerning synthesis of new cryptosystems equivalent to SAFER+ and SAFER++ to perform their linear cryptanalysis in the cluster computational environment. A parallel software package “LinearCryptanalyser” is developed to find such "Armenian Shuffles" which were chosen as secure against differential cryptanalysis and now will be checked if they are also secure against linear cryptanalysis. The research is focused on both theoretical and practical aspects of existence of linked I/O sums. The software package “LinearCryptanalyser” analyzes the existence of linked I/O sums and the absence of such sums will indicate cryptоresistance of block ciphers against last-round attack.